Inhibition of the Proliferation of Human Lung Fibroblasts by Prostacyclin Receptor Agonists is Linked to a Sustained cAMP Signal in the Nucleus - Roberts, Maxine J.; May, Lauren T.; Keen, Alastair C.; Liu, Bonan; Lam, Terrance; Charlton, Steven J.; Rosethorne, Elizabeth M.; Halls, Michelle L. (Frontiers in Pharmacology, 2021)
Idiopathic pulmonary fibrosis is a chronic and progressive fibrotic lung disease, and current treatments are limited by their side effects. Proliferation of human lung fibroblasts in the pulmonary interstitial tissue is a hallmark of this disease and is driven by prolonged ERK signalling in the nucleus in response to growth factors such as platelet-derived growth factor (PDGF). Agents that increase cAMP have been suggested as alternative therapies, as this second messenger can inhibit the ERK cascade. We previously examined a panel of eight Galphas-cAMP-coupled G protein-coupled receptors (GPCRs) endogenously expressed in human lung fibroblasts. Although the cAMP response was important for the anti-fibrotic effects of GPCR agonists, the magnitude of the acute cAMP response was not predictive of anti-fibrotic efficacy. Here we examined the reason for this apparent disconnect by stimulating the Galphas-coupled prostacyclin receptor and measuring downstream signalling at a sub-cellular level. MRE-269 and treprostinil caused sustained cAMP signalling in the nucleus and complete inhibition of PDGF-induced nuclear ERK and fibroblast proliferation. In contrast, iloprost caused a transient increase in nuclear cAMP, there was no effect of iloprost on PDGF-induced ERK in the nucleus, and this agonist was much less effective at reversing PDGF-induced proliferation. This suggests that sustained elevation of cAMP in the nucleus is necessary for efficient inhibition of PDGF-induced nuclear ERK and fibroblast proliferation. This is an important first step towards understanding of the signalling events that drive GPCR inhibition of fibrosis.